2013
DOI: 10.1007/s00038-013-0529-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific changes in physical activity pattern in Iran: national surveillance of risk factors of non-communicable diseases (2007–2011)

Abstract: This report indicating that the Iranian population, particularly females, have become less active during the survey period. Physical inactivity should receive more attention as a public health issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 34 publications
7
44
1
3
Order By: Relevance
“…Furthermore, work-related activity was dramatically decreased in women. 28 The present results regarding the prevalence and trend of CVD risk factors were considerably different between the two sexes. The difference in the prevalence and the trend of the CVD risk factors between men and women was also shown in our previous studies in the same population.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, work-related activity was dramatically decreased in women. 28 The present results regarding the prevalence and trend of CVD risk factors were considerably different between the two sexes. The difference in the prevalence and the trend of the CVD risk factors between men and women was also shown in our previous studies in the same population.…”
Section: Discussioncontrasting
confidence: 53%
“…According to Iran's national surveys carried out on 2007 and 2011, the Iranian population, particularly women, has become less active. Furthermore, work‐related activity was dramatically decreased in women …”
Section: Discussionmentioning
confidence: 99%
“…Living in an urban area was positively associated with total SB in all East Asian (Chinese) samples. 53,59,60,97 In contrast, studies from South-East Asia 92 and the Middle East, 82,87 as well as three out of four studies in South Asians, reported no relationships between urban residency and total SB. 53,93,96,97 Urban residence was unrelated to occupational and transport-related SB based on one study from Oman, 83 while it was positively associated with leisure-time SB according to one Chinese study.…”
Section: Residential Area Correlatesmentioning
confidence: 91%
“…[2] Studies show that the prevalence of immobility among the population 22–65 years during the 4 years has increased from 15% (1385) to 21.5% (1390) and the rate of immobility in work, travel and traffic, and recreation and leisure time have been 56.4%, 39.2% and 78.7%, respectively. [3] Moreover, evidences show that 70–80% of Iranians do not have enough mobility[45] that its statistics in Iranian women is far higher than Iranian men. [6] In a study conducted in Tehran, 69.8% of the study population was inactive; in other words, only 3.30% of the women were doing physical activity.…”
Section: Introductionmentioning
confidence: 99%